Natural Killer Cells Regulate Th17 Cells After Autologous Hematopoietic Stem Cell Transplantation for Relapsing Remitting Multiple Sclerosis - Darlington, Peter J.; Stopnicki, Brandon; Touil, Tarik; Doucet, Jean-Sebastien; Fawaz, Lama; Roberts, Morgan E.; Boivin, Marie-Noëlle; Arbour, Nathalie; Freedman, Mark S.; Atkins, Harold L.; Bar-Or, Amit (Frontiers in Immunology, 2018)
In autoimmunity, the balance of different helper T cell (Th) subsets can influence the tissue damage caused by autoreactive T cells. Pro-inflammatory Th1 and Th17 T cells are implicated as mediators of several human autoimmune conditions such as multiple sclerosis (MS). Autologous hematopoietic cell transplantation (aHSCT) has been tested in phase 2 clinical trials for MS patients with aggressive disease. Abrogation of new clinical relapses and brain lesions can be seen after ablative aHSCT, accompanied by significant reductions in Th17, but not Th1, cell populations and activity. The cause of this selective decrease in Th17 cell responses following ablative aHSCT is not completely understood. We identified an increase in the kinetics of natural killer cell (NK) reconstitution, relative to CD4+ T cells, in MS patients post aHSCT, resulting in an increased NK cell:CD4+ T cell ratio that correlated with the degree of decrease in Th17 responses. Ex vivo removal of NK cells from post-aHSCT PBMCs resulted in higher Th17 cell responses, indicating that NK cells can regulate Th17 activity. NK cells were also found to be cytotoxic to memory Th17 cells, and that this toxicity is mediated through NKG2D-dependent necrosis. Surprisingly, NK cells induced memory T cells to secrete more IL-17A. This was preceded by an early rise in T cell expression of RORC and IL17A mRNA, and could be blocked with neutralizing antibodies against CD58, a co-stimulatory receptor expressed on NK cells. Thus, NK cells provide initial co-stimulation that supports the induction of a Th17 response, followed by NKG2D-dependent cytotoxicity that limits these cells. Together these data suggest that rapid reconstitution of NK cells following aHSCT contribute to the suppression of the re-emergence of Th17 cells. This highlights the importance of NK cells in shaping the reconstituting immune system following aHSCT in MS patients.